The Mechanism Underlying the Association of School Climate and Reading Achievement: The Mediating Role of Intrinsic Motivation and Reading Self-Concept in the Greek Context - Katsantonis, Ioannis (Technium Social Sciences Journal, 2020)
The association between school climate and students’ achievement is currently well-documented in international literature. However, the relevant studies, that contemplate the underlying mechanisms of this association, are sparse. Therefore, the present study’s purpose is to confirm the mediating effects of intrinsic motivation and reading self-concept in the association of school climate and reading achievement. Further, due to the amassing evidence of gender-related individual differences in academic achievement, this study also examines whether the underlying mechanisms toward academic achievement are varying as a function of gender. The data of N=6,403 Greek adolescent students were extracted from the Program of International Student Assessment (PISA) for further analyses. Structural equation modeling (SEM) was conducted to examine both mediating and moderating effects. The results indicate that there is a positive indirect effect of school climate on reading achievement via intrinsic motivation and self-concept. Additionally, structural equivalence via multigroup SEM (MGSEM) showed that gender does not moderate the structural regressive relations; that is, the regression coefficients did not vary as a function of gender. These findings are discussed within the framework of improving educational practices.